2017
DOI: 10.1007/s13592-017-0540-4
|View full text |Cite
|
Sign up to set email alerts
|

The ontogenetic saga of a social brain

Abstract: -Queen and worker honeybees differ in a number of life-history traits, including the size of certain brain regions, such as the mushroom bodies (MBs), which are larger in workers. However, during the larval period, the differential feeding offered to queens promotes faster brain development. As a result, members of this caste have larger brains than workers. This developmental process is accompanied by the higher expression of several neurogenic genes. Nonetheless, a caste-specific shift in relative brain grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 109 publications
1
15
0
1
Order By: Relevance
“…B). Moreover, we suggest that ftz‐f1 can also be considered a competence factor to the expression of several additional genes in the pharate‐adult hormonal environment, thus acting as a key player in one of the last developmental processes leading to caste differentiation in A. mellifera (Barchuk et al ., ): first, because ftz‐f1 has a caste‐specific transcription profile in the fat body at the end of the pharate‐adult development, showing differential peak levels between castes just at the moment of the JH titres increase in the presence of declining levels of ecdysteroids; and second, because knock‐down experiments showed that the expression of genes essential to this critical developmental period (e.g. vg , but not pro‐PO or jhe ) depends on ftz‐f1 .…”
Section: Discussionmentioning
confidence: 99%
“…B). Moreover, we suggest that ftz‐f1 can also be considered a competence factor to the expression of several additional genes in the pharate‐adult hormonal environment, thus acting as a key player in one of the last developmental processes leading to caste differentiation in A. mellifera (Barchuk et al ., ): first, because ftz‐f1 has a caste‐specific transcription profile in the fat body at the end of the pharate‐adult development, showing differential peak levels between castes just at the moment of the JH titres increase in the presence of declining levels of ecdysteroids; and second, because knock‐down experiments showed that the expression of genes essential to this critical developmental period (e.g. vg , but not pro‐PO or jhe ) depends on ftz‐f1 .…”
Section: Discussionmentioning
confidence: 99%
“…fornicatus transcriptome, 100 were expressed in the whole body, 45 were enriched or specific for abdomen and 19 for head-thorax (see Table S6 for more details). Signals of selection were found on the sex peptide receptor [126,127] and galactosylgalactosylxylosyl protein 3-beta-glucuronosyltransferase P (GlcAT-P; [128]) genes, which are exclusively transcribed on the head-thorax. Particularly, genes under selection are significantly enriched ( p ≤ 0.01 in Fisher’s exact test) in the GO functional categories of fructose metabolism (GO:0006000) in E. nr.…”
Section: Resultsmentioning
confidence: 99%
“…fornicatus and X. glabratus suggest an adaptive evolution in the ambrosia beetles towards changes in behavior. Among these genes, we found several proteins conserved in mammals and insects required for synaptogenesis (amphysin, liprin, neuroligin-2, neurexin-4, SLIT-NTRK protein 1, GlcAT-P; [128,152,153,154], nervous system development (neuronal PAS-domain-containing protein 4, Neural/ectodermal development factor, IMP-L2; [155,156], neurotransmitter transport, (sodium neurotransmitter symporter; [157] and, as previously mentioned, development of sensory organs (basic helix-loop-helix amos transcription factor and suppressor of hairless protein [158,159,160]. Neuroligin-2 has been directly associated with social behavior in D. melanogaster [161] and GlcAT-P shows caste-specific transcriptional patterns during brain development in Apis mellifera [128].…”
Section: Discussionmentioning
confidence: 99%
“…Honeybee workers have larger antennal lobes and mushroom bodies than queens and also have special tool-like organs, such as a pollen press and a corbicula, a long proboscis, large hypopharyngeal and mandibular glands, wax glands, Nasanov's gland and a straight and barbed sting (Wilson, 1971;Michener, 1974). All these characteristics constitute a suit of sensory-effector armamentarium for workers to cope with the broad range of duties they need to perform in a colony, such as nursing the brood, nest building and cleaning, nestmate recognition and guarding and foraging (Menzel, 2014;Barchuk et al, 2018). On the other hand, to cope with their reproductive duty, honeybee queens feature a morphophysiological set of characteristics, including large spermatheca and ovaries and pheromone-secreting glands for the control of the workers' behaviour (Snodgrass 1910;Michener, 1974;Barchuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%